Rationale for selecting the type of grinding balls in energy-efficient invariant control of ore comminution - Khliebnikov, Mykola; Matsui, Anatolii; Les, Yaroslav (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This publication is devoted to the rationale of the choice of high-hardness grinding balls and the implementation of energy-efficient invariant control measures for ore comminution processes in the first-stage ball mills, ensuring reduced energy consumption and increased mill productivity. Дана публікація присвячена обґрунтуванню вибору типу молольних куль підвищеної твердості та заходів енергоефективного інваріантного керування процесом подрібнення руд у кульових млинах першої стадії, що забезпечує зниження енерговитрат і підвищення продуктивності кульових млинів.